MODELLING NON-LINEAR STRESS RELAXATION OF POLY(ETHYLENE TEREPHTHALATE) - André, José Reinas (2017)
The models presented in the literature to interpret the behavior of polymeric materials at stress relaxation stresses are essentially empirical or semi-empirical, not taking into consideration the physical (molecular) mechanisms responsible for the viscoelastic behavior. In the present study, a previously developed molecular model [1, 2] was applied with the purpose of describing the stress relaxation of polymeric materials, at various deformations and different temperatures, with and without previous heat treatment.